C-reactive protein in acute coronary syndrome: association with 3-year outcomes - Schaan,B.D. (2009)
Inflammatory markers have been associated with clinical outcome in patients with acute coronary syndrome (ACS). The present study evaluated the role of high-sensitivity C-reactive protein (CRP) measurements as a predictor of late cardiovascular outcomes after ACS. One hundred and ninety-nine ACS patients in a Coronary Care Unit from March to November 2002 were included and were reassessed clinically after ~3 years. Clinical variables and CRP levels were evaluated as predictors of major cardiovascular events (MACE, defined as the occurrence of cardiac death, ischemic stroke or myocardial infarction) and mortality. Statistical analyses included Cox multivariable analysis and survival curves (Kaplan-Meier). Of the 199 patients, 11 died within 1 month (5.5%). Of the 188 remaining patients, 22 died after a mean follow-up of 2.9 ± 0.5 years. Baseline CRP levels for patients with MACE (N = 57) were significantly higher than those of patients with no events (median = 0.67 mg/L; 25th-75th percentiles = 0.32 and 1.99 mg/L vs median = 0.45 mg/L; 25th-75th percentiles = 0.24 and 0.83 mg/L; P < 0.001). Patients with CRP levels >3 mg/L had a significantly lower survival than the other two groups (1-3 and <1 mg/L; P = 0.001, log-rank test). The odds ratio for MACE was 7.41 (2.03-27.09) for patients with CRP >3 mg/L compared with those with CRP <1 mg/L. For death by any cause, the hazard ratio was 4.58 (1.93-10.86). High CRP levels predicted worse long-term outcomes (MACE and death by any cause) in patients with ACS.